1975 Fisheries Survey of Torch Lake, Antrim County - Michigan Department of Natural Resources; Alward, Warren (2013)
Partial OCR done. Partially handwritten. 17 pages total. This survey was initiated to evaluate an increased lake trout stocking program begun in 1969. Although lake trout are native to Torch Lake, limited fry, fingerling, yearling or legal-size fish stocking has continued since 1895. In October, 1975, the fish population of Torch Lake, Antrim County was surveyed with standard Great Lakes gill net gangs. Index stations were established and sampling gear was standardized so year-to-year comparisons of species abundance could be made. Lake trout (66 percent of the catch by weight) followed by cisco and whitefish were the most abundant species collected in the survey. The catch of lake trout per 1,000 feet of gill net compared favorably with similar netting efforts in Lake Michigan during 1975. Lake trout catch per 1,000 feet of net for Torch Lake and Lake Michigan were 20.3 and 17.6 respectively.